PENGARUH PROMOSI DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK ELEKTRONIK DI SHOPEE - Nurmala, Putri; Widiyanti, Wiwik; Susilowati, Isnurrini Hidayat; Marginingsih, Ratnawaty (Politeknik Negeri Ambon, 2025)
Introduction: The rapid development of digital information systems has shifted shopping patterns from traditional offline activities toward online transactions. Shopee, as a central e-commerce platform in Indonesia, implements promotional programs and utilizes user-generated reviews, both of which play a crucial role in shaping consumer purchasing behavior, especially for high-value electronic products. This study investigates the influence of promotions and online reviews, either individually or in combination, on purchasing decisions.Methods: A quantitative approach was applied, involving 198 respondents residing in the Greater Jakarta region who had experience buying electronic products through Shopee. Data were gathered using an online questionnaire and analyzed with multiple linear regression through SPSS version 27Results: The findings indicate that promotions have a significant influence on consumer purchasing, with a regression coefficient of 0.230 (p < 0.05). This considerable effect occurs because promotional programs, such as discounts, cash back, and free shipping, create a psychological stimulus that increases consumers’ desire and urgency to purchase electronic products. In comparison, online reviews provide a more substantial impact, reflected by a regression coefficient of 0.416 (p < 0.05). The more significant influence of online customer reviews stems from the fact that credible and detailed reviews enhance consumer trust, reduce perceived risk, and serve as a form of social proof that validates product quality. When considered together, both variables demonstrate a significant effect on purchasing outcomes (p < 0.05), with an R² value of 0.641. These results suggest that Shopee and similar e-commerce platforms should strengthen their promotional strategies and effectively manage online reviews to build consumer confidence and increase purchasing decisions for electronic products. Keywords: Promotion, Online Customer Review, Purchase Decision, E-commerce, Electronic Products.